OCCURRENCE OF THE GREEN MUSSEL PERNA VIRIDIS (LINNAEUS) IN ANDAMAN ISLAND - Appukkuttan, K K (Indian Journal of Fisheries, 2011)
Information on the molluscan fauna of Andaman and Niooba1." Islands is sc,a,rce. In the published works on the moHuscs of this area, Meivin and Sykes (1897, 1899, 1899a), Setna (1932), Winckworth (1933), Prashad and Rao (1934), Sastri (1939), Ray (1949) and Rajagopal and Rao (1974), no mention has heen made of the occurrence of Perna from thLs IsIand.